2017
DOI: 10.1063/1.5006958
|View full text |Cite|
|
Sign up to set email alerts
|

Differential voltage amplification from ferroelectric negative capacitance

Abstract: It is well known that one needs an external source of energy to provide voltage amplification. Because of this, conventional circuit elements such as resistors, inductors or capacitors cannot provide amplification all by themselves. Here, we demonstrate that a ferroelectric can cause a differential amplification without needing such an external energy source. As the ferroelectric switches from one polarization state to the other, a transfer of energy takes place from the ferroelectric to the dielectric, determ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 25 publications
(33 reference statements)
2
11
0
Order By: Relevance
“…Since the electric field inside the ferroelectric layer of the MIMFM structure is determined by the apparent polarization irrespective of the spatial configuration of the multidomain state, there is theoretically no difference between the NC stabilization method for the single domain state and the multidomain state except that the latter has a L crit limit. Experimentally, while Khan et al recently found a differential voltage amplification by connecting DE capacitors to an epitaxial PZT FE thin film capacitor via a metal wire externally, it was a transient effect with a hysteresis . The experiment showed that the DE layer plays a role nothing but a linear load line for a typical square‐like P − V hysteresis of the ferroelectrics (except that it has a transient V ‐drop at the switching in each direction) in the MIMFM structure.…”
Section: Mimfm Versus Mfim (Mifim) Systemmentioning
confidence: 96%
“…Since the electric field inside the ferroelectric layer of the MIMFM structure is determined by the apparent polarization irrespective of the spatial configuration of the multidomain state, there is theoretically no difference between the NC stabilization method for the single domain state and the multidomain state except that the latter has a L crit limit. Experimentally, while Khan et al recently found a differential voltage amplification by connecting DE capacitors to an epitaxial PZT FE thin film capacitor via a metal wire externally, it was a transient effect with a hysteresis . The experiment showed that the DE layer plays a role nothing but a linear load line for a typical square‐like P − V hysteresis of the ferroelectrics (except that it has a transient V ‐drop at the switching in each direction) in the MIMFM structure.…”
Section: Mimfm Versus Mfim (Mifim) Systemmentioning
confidence: 96%
“…The question remains whether the negative curvature of the free energy has to be involved in this process 37,39,[46][47][48] . A variant of this direct method to moni tor transient NC is to replace the series resistor with an external series capacitance 105 ; the capacitor then directly controls the charge on the ferroelectric, as originally proposed by Salahuddin and Datta 10 .…”
Section: Evidence For Transient Ncmentioning
confidence: 99%
“…This means that finite polarization switching delay is responsible for TNC [17]. In fact, TNC was experimentally demonstrated in an FE-DE series capacitor in [27].…”
Section: B Tnc In Fe-de Series Capacitorsmentioning
confidence: 99%